Pembuatan Batu Bata Dengan Penambahan Tanah Terkontaminasi Minyak - Annisa Aprilya Putri; Ahmad Fadli; Cory Dian Alfarisi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The petroleum industry is one of the largest oil and gas companies in Indonesia. From the exploration and production of petroleum, it turns out that the petroleum industry also produces petroleum waste which can pollute the soil. For waste handling, it is necessary to have efficient and environmentally friendly petroleum processing, in the form of brick making. The purpose of this study was to study the effect of adding a mixture of oil and clay contaminated soil and the effect of drying time on the bricks obtained from the tests carried out, namely testing compressive strength, density, water absorption, and porosity. The procedure was started with weighing all materials with variations of 2 kg, 10 kg and 14 kg oil-contaminated soil (TTM), mixing oil and cement, and then stirring water until it was homogeneous. the next step has been the processed of molding the stones and then drying them for 3, 5 and 7 days and finally the burning process has been carried out. Variations were studied by differentiating the percentage composition of the soil mixture contaminated with oil and clay used. The test results from the compressive strength, density, absorption and porosity test show that the best sample for consumers is the sample with 2 Kg oil-contaminated soil on drying for 7 days while the best sample in terms of utilization is the sample with the composition of 14 Kg oil-contaminated soil.Keywords: brick, compressive strength, porosity, oil contaminated soil